PEST MONITORING ON PLANTS LONG BEANS (VIGNA UNGUICULATA L) - Bambang Prasetio; Teguh Akbar Sitorus; Jalali Ikhromi; Fachri Ambiya; Syafiq Al-Ayuby; Taufik Hidayat; Dimas Mahendra (ITScience (Information Technology and Science), 2022)
Peanut long has Mark commercial tall and have a very big role in fulfilling need food nutrition society, especially to vegetable protein requirements. Plant this could grow and produce with good want characteristic physical loose soil, depth soil enough in To increase productivity farmer vegetable peanuts long do control pest with depending on spraying insecticide synthetic because considered more effective and efficient in its use. The aim of this research is for knowing type pests found in gardens long beans in the area Plantation Village of the District of Young Development North Batu Labuan. Result observation could be used as a base in taking control action pests by farmers. The observation was done on tana man peanut in the village of plantations in the district of Membang Muda Labuhan Batu Utara from April until June 2021. Map observed sample of 1x1 m. Observation conducted with use monitoring method. Observation data is noted every week. The result from this observation obtained that pests on plants long beans observed in the Plantation Village of Membang Muda District Labuhan Batu Utara is an aphid Aphids croccivora, and caterpillars borer Maruca testicular. Average attack both 0.83 and 5. Population pest most in the area there is caterpillar borer Maruca testicular. Pest Control Measures could be conducted with spraying chemicals or technical culture. Pest monitoring urgent conducted as base taking decision technical control.